LINGUISTIC AND SOCIAL ASPECTS OF NAME GIVING MOTIVATION - dos Santos, Núbia Caroline (Espaço Plural, 2018)
Olesya V. Kisel[1] Natalya N. Zerkina[2] Yuliya A. Savinova [3] Tatyana Y. Zalavina[4] Natalya V.Kozhushkova[5] Vladimir V. Mikhaylov[6] Abstract: The article deals with the problem of influence of social factors on the name giving process with taking into account their motivation. The authors carry out a survey by means of the questionnaire, specify and prove the existing theory of social origin of name giving process motivation. Onyms are considered as linguistic units, and the process of changing their semantic structure under the influence of their social factors is studied. For detailed studying of the subject, a complex analysis was carried out, which includes such techniques as comparison, classification and evaluation. The research is relevant in the linguistic, social, national and cognitive aspects, as it demonstrates an interaction between language and society. As a result, social motives of name giving process were classified that determine future development of anthroponymicon. Keywords: onym; name giving process; onomastic; social motives; onomastic universalia; anthroponym; national motivation; name giving; religious motivation; ideological motivation. [1] PhD in Linguistics, Associate Professor, Foreign Languages for Engineering Chair Institute of Humanities Nosov Magnitogorsk State Technical University [2] PhD in Linguistics, Associate Professor, Foreign Languages for Engineering Chair Institute of Humanities Nosov Magnitogorsk State Technical University [3]PhD in Pedagogy, Associate Professor, Department of Foreign Languages for Engineering Chair Institute of Humanities Nosov Magnitogorsk State Technical University [4] PhD in Linguistics, Associate Professor, Foreign Languages for Engineering Chair, Institute of Humanities, Nosov Magnitogorsk State Technical University, [5] PhD in Linguistics, Associate Professor, Department of Sociology, Document Science and Archive Science, Institute of Humanities, Nosov Magnitogorsk State Technical University [6] PhD in Pedagogy, Associate Professor, Department of Foreign Languages for Engineering Chair Institute of Humanities Nosov Magnitogorsk State Technical University